The impact of mindfulness intervention on the subjective well-being of nursing students: an experimental study - Nurgul Karakurt; Hatice Durmaz (BMC Psychology)
Abstract Background Nursing students frequently encounter significant psychological stressors during their education, placing them at increased risk for reduced subjective well-being and mental health challenges. Mindfulness-Based Stress Reduction programs have emerged as promising interventions to enhance psychological resilience and well-being in this vulnerable population. Methods This experimental study utilized a pretest–posttest design with experimental and control groups. A total of 60 nursing students participated, with 30 assigned to the experimental group and 30 to the control group. Nursing students’ subjective well-being was assessed using the Subjective Well-Being Scale before and after the intervention. The experimental group participated in an eight-week Mindfulness-Based Stress Reduction program adapted from Kabat-Zinn’s model, consisting of two 30-40-minute sessions per week, while the control group received no intervention. Data were analyzed using independent samples t-tests to compare differences between groups and paired samples t-tests for within-group changes. Results No significant difference was observed in pretest subjective well-being scores between the groups (p > 0.05). Post-intervention analysis revealed a statistically significant increase in subjective well-being scores in the experimental group compared to the control group (p < 0.001). Within-group comparisons showed a significant improvement in subjective well-being for the experimental group, while the control group exhibited a decline (p < 0.001). Conclusions Participation in an eight-week Mindfulness-Based Stress Reduction program significantly improved the subjective well-being of nursing students, suggesting its potential as an accessible and effective intervention for supporting their mental health. These findings underscore the importance of integrating mindfulness-based programs into nursing education to promote resilience and prevent emotional exhaustion.